Biallelic variants in GTF3C3 result in an autosomal recessive disorder with intellectual disability. - De Hayr, L.; Blok, L.E.R.; Dias, K.R.; Long, J.; Begemann, A.; Moir, R.D.; Willis, I.M.; Mocera, M.; Siegel, G.; Steindl, K.; Evans, C.A.; Zhu, Y.; et al. (Genetics in medicine, 2025)
This study details a novel syndromic form of autosomal recessive intellectual disability resulting from recessive variants in GTF3C3, encoding a key component of the DNA-binding transcription factor IIIC, which has a conserved role in RNA polymerase III-mediated transcription. Exome sequencing, minigene analysis, molecular modeling, RNA polymerase III reporter gene assays, and Drosophila knockdown models were utilized to characterize GTF3C3 variants. Twelve affected individuals from 7 unrelated families were identified with homozygous or compound heterozygous missense variants in GTF3C3 including c.503C>T p.(Ala168Val), c.1268T>C p.(Leu423Pro), c.1436A>G p.(Tyr479Cys), c.2419C>T p.(Arg807Cys), and c.2420G>A p.(Arg807His). The cohort presented with intellectual disability, variable nonfamilial facial features, motor impairments, seizures, and cerebellar/corpus callosum malformations. Consistent with disruptions in intra- and intermolecular interactions observed in molecular modeling, RNA polymerase III reporter assays confirmed that the majority of missense variants resulted in a loss of function. Minigene analysis of the recurrent c.503C>T p.(Ala168Val) variant confirmed the introduction of a cryptic donor site into exon 4, resulting in mRNA missplicing. Consistent with the clinical features of this cohort, neuronal loss of Gtf3c3 in Drosophila induced seizure-like behavior, motor impairment, and learning deficits. These findings confirm that GTF3C3 variants result in an autosomal recessive form of syndromic intellectual disability.